2021
DOI: 10.3390/ani11030748
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Morphokinetic Parameters of Feline Embryos Using a Time-Lapse System

Abstract: The aim of this study was to analyze the morphokinetic parameters of feline embryos using a time lapse system. Oocytes matured in vitro were fertilized (IVF) and in vitro cultured in a time lapse-system (Primo Vision®, Gothenburg, Sweden). The first cell division of embryos occurred between 17 h post insemination (hpi) and 38 hpi, with the highest proportion of embryos (46%) cleaving between 21 and 24 hpi. The timing of the first cleavage significantly affected further embryo development, with the highest deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…The results presented in our study indicate a similar number of blastocysts (P=0.050948) and hatching blastocysts (P= 0.5) developed from regular and irregular shaped presumptive zygotes, despite significant differences in the number of embryos (P= 0.000319) developed from such zygotes. In another study, the average diameters of the oocytes of the domestic cat, Pallas cat, lynx, and serval were all found to be approximately 161±4 μm (Kochan et al, 2021 b). Here, we measured the diameter of the PZ, but assuming no differences between the diameters of oocytes and zygotes, these results should be comparable, and we found an average PZ diameter of 161.37±17.42 μm.…”
Section: Discussionmentioning
confidence: 46%
“…The results presented in our study indicate a similar number of blastocysts (P=0.050948) and hatching blastocysts (P= 0.5) developed from regular and irregular shaped presumptive zygotes, despite significant differences in the number of embryos (P= 0.000319) developed from such zygotes. In another study, the average diameters of the oocytes of the domestic cat, Pallas cat, lynx, and serval were all found to be approximately 161±4 μm (Kochan et al, 2021 b). Here, we measured the diameter of the PZ, but assuming no differences between the diameters of oocytes and zygotes, these results should be comparable, and we found an average PZ diameter of 161.37±17.42 μm.…”
Section: Discussionmentioning
confidence: 46%
“…As previously demonstrated by Jeong et al (2009), oocyte color, as a measure of lipid content, can be predictive of embryo developmental potential. Kochan et al (2021a, b) have shown that oocytes with light cytoplasm were significantly smaller than oocytes with dark cytoplasm in adult and prepubertal cats. Low light permeation of oocytes reflects their high lipid content (Jeong et al, 2009).…”
Section: Discussionmentioning
confidence: 94%